Qur'anic Character Education in the Digital Era: Integrating the Roles of Schools and Families in Children's Moral Development - Rizqianto Hermawan; Mahasri Shobahiya (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Character education is a learning process designed to instill moral values in individuals, aiming to build a noble personality, maintain integrity, and behave in accordance with prevailing social norms. Its primary focus is not only on teaching moral concepts but also on developing attitudes and behaviors that reflect these values in everyday life. This study aims to analyze the role of schools and families in shaping Qur'anic character education in the digital era. The primary focus of this research is integrating digital technology with Islamic values in learning, both in schools and at home. The method used is descriptive qualitative, with data collection techniques through interviews and observations. The results show that schools play a strategic role in integrating Qur'anic values into the curriculum through the use of digital media such as learning applications and interactive videos. However, the main challenge faced is the lack of teacher training in effectively managing technology to support character education. On the other hand, families act as primary supervisors and mentors who help children apply Qur'anic values at home. Nevertheless, many parents find it difficult to implement consistent and effective digital parenting strategies. The implications of this study emphasize the importance of synergy between schools and families to create a conducive environment for children's moral development. Recommendations include teacher training, the development of digital parenting strategies, and further research on the effectiveness of technology-based learning methods in Qur'anic character education.